Impact of easing COVID-19 lockdown restrictions on traumatic injuries in Riyadh, Saudi Arabia: one-year experience at a major trauma centre - Rayan Jafnan Alharbi; Rami Al-Jafar; Sharfuddin Chowdhury; Muhammad Aziz Rahman; Ateeq Almuwallad; Abdullah Alshibani; Virginia Lewis (BMC, 2023)
Abstract Introduction Lockdown restrictions due to the COVID-19 pandemic have reduced the number of injuries recorded. However, little is known about the impact of easing COVID-19 lockdown restrictions on the nature and outcome of injuries. This study aims to compare injury patterns prior to and after the easing of COVID-19 lockdown restrictions in Saudi Arabia. Method Data were collected retrospectively from the Saudi TraumA Registry for the period between March 25, 2019, and June 21, 2021. These data corresponded to three periods: March 2019-February 2020 (pre-restrictions, period 1), March 2020-June 2020 (lockdown, period 2), and July 2020-June 2021 (post easing of restrictions, period 3). Data related to patients' demographics, mechanism and severity of injury, and in-hospital mortality were collected and analysed. Results A total of 5,147 traumatic injury patients were included in the analysis (pre-restrictions n = 2593; lockdown n = 218; post easing of lockdown restrictions n = 2336). An increase in trauma cases (by 7.6%) was seen in the 30-44 age group after easing restrictions (n = 648 vs. 762, p < 0.01). Motor vehicle crashes (MVC) were the leading cause of injury, followed by falls in all the three periods. MVC-related injuries decreased by 3.1% (n = 1068 vs. 890, p = 0.03) and pedestrian-related injuries decreased by 2.7% (n = 227 vs. 143, p < 0.01); however, burn injuries increased by 2.2% (n = 134 vs. 174, p < 0.01) and violence-related injuries increased by 0.9% (n = 45 vs. 60, p = 0.05) post easing of lockdown restrictions. We observed an increase in in-hospital mortality during the period of 12 months after easing of lockdown restrictions-4.9% (114/2336) compared to 12 months of pre-lockdown period-4.3% (113/2593). Conclusion This is one of the first studies to document trauma trends over a one-year period after easing lockdown restrictions. MVC continues to be the leading cause of injuries despite a slight decrease; overall injury cases rebounded towards pre-lockdown levels in Saudi Arabia. Injury prevention needs robust legislation with respect to road safety measures and law enforcement that can decrease the burden of traumatic injuries.